2020
DOI: 10.1177/1178646920972657
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tryptophan 2,3-Dioxygenase Inhibition on Kynurenine Metabolism and Cognitive Function in the APP23 Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is associated with progressive endogenous neurotoxicity and hampered inflammatory regulation. The kynurenine (Kyn) pathway, which is controlled by tryptophan 2,3-dioxygenase (TDO), produces neuroactive and anti-inflammatory metabolites. Age-related Kyn pathway activation might contribute to AD pathology in humans, and inhibition of TDO was found to reduce AD-related cellular toxicity and behavioral deficits in animal models. To further explore the effect of aging on the Kyn pathway in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Regarding the molecular and biochemical differences underlying these opposing results a straightforward explanation could be that AD mice and LPS treated animals show differences regarding the responsiveness for TDO inhibitory treatment. However, TDO inhibition did not affect kynurenine metabolite levels either in brains of APP23 mice or LPS-treated animals [63,64]. Thus further research is needed in order to clarify the exact mode of action of TDO inhibition on cognitive functions.…”
Section: Tdo and Neurodegenerative Diseasesmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the molecular and biochemical differences underlying these opposing results a straightforward explanation could be that AD mice and LPS treated animals show differences regarding the responsiveness for TDO inhibitory treatment. However, TDO inhibition did not affect kynurenine metabolite levels either in brains of APP23 mice or LPS-treated animals [63,64]. Thus further research is needed in order to clarify the exact mode of action of TDO inhibition on cognitive functions.…”
Section: Tdo and Neurodegenerative Diseasesmentioning
confidence: 94%
“…In recent reports Woodling et al and Sorgdrager and colleagues reported that pharmacological inhibition of TDO improved cognitive performance of APP23 and APP-PS1 AD mice by reversing recognition memory deficits of the animals [62,63]. However, anxiety and cognitive dysfunction provoked with lipopolysaccharide (LPS) stress were not prevented by pharmacological TDO inhibition in this mouse model [64].…”
Section: Tdo and Neurodegenerative Diseasesmentioning
confidence: 96%
“…In turn, preclinical studies indicate that targeting KMO in neurological disorders is a more efficient and safe solution [11,198]. [11,68,151,163,199,200] Indoleamine 2,3-dioxygenase (IDO, EC 1.13.11.17)…”
Section: Kynurenine 3-monooxygenasementioning
confidence: 99%
“…In turn, Kanai et al demonstrated that TDO modulates anxiety-related behavior in mice, while Campesan et al showed that inhibition of TDO activity, by silencing its gene, and protects against the severity of HD symptoms in the transgenic Drosophila melanogaster model [ 163 , 200 , 209 ]. In turn, Sorgdrager et al proved that long-term administration of 680C91, the oral inhibitor of TDO, significantly reversed recognition memory deficits in the mouse model of AD, however without affecting spatial learning and memory or anxiety-related behavior [ 199 ]. Moreover, preclinical studies also found that its inhibition is effective in alleviating depressive symptoms, which are also, to some extent, associated with an increase in oxidative stress levels caused by inflammation and KP overactivity in neurons ( Table 2 ) [ 68 , 151 , 200 ].…”
Section: Enzymes Of the Kynurenine Pathway And The Possibility Of Pharmacological Modulation Of Their Activitymentioning
confidence: 99%
“…Similar to AD patients and Tg2576 mice, APP23 mice exhibit amyloid angiopathy in the cerebral vessels [ 81 ]. Additionally, APP23 Tg mice display age-related abnormal phenotypes associated with cognitive function in various behavioral tests [ 82 , 83 , 84 , 85 , 86 ]. These phenotypes in APP23 mice are similar to all symptoms observed in AD patients.…”
Section: Biomarkers and Amyloid Cascade Hypothesis-related Animal Modelsmentioning
confidence: 99%